Machiavelli a very short introduction - Skinner, Quentin 1940- (Very short introductions, 2019)
Machiavelli taught that political leaders must be prepared to do evil that good may come of it. Because of this he has gained a sinister reputation. Focusing on 3 major works, Skinner distils from them an introduction to Machiavelli's doctrines of clarity